Perjumpaan Penginjil CGK Belanda Dengan Orang Toraja Mamasa: Praktik Metode Penginjilan Arie Bikker Dan Martin Geleijnse serta Relevansinya Bagi Metode Pekabaran Injil Gereja Toraja Mamasa Masa Kini - abialtar (Institut Agama Kristen Negeri Toraja, 2020)
Preaching the gospel by Western mission organizations has given rise to a unique encounter between missionaries and indigenous peoples where they preach the gospel. The problem that arises then is the lack of research into what this encounter is and what it means for church life today. The author examines the encounter of evangelists from de Christelijke Gereformeerde Kerken (CGK) in the Netherlands with the Toraja Mamasa community, especially the To Salu tribe with qualitative research methods by relying on library research and mission history archives in Mamasa. Also conducted interviews with traditional and church leaders in Mamasa. The author found that the encounter between the two evangelists with the To Salu tribe had resulted in a missionary attitude and insight and certain theological characteristics which were then inherent in the history of the Toraja Mamasa Church (GTM) which was the fruit of the CGK evangelism. The author's thesis statement: